Analysis of Digital IIR Filter Using LabVIEW - Tripathi, Sweta (My University, 2010)
In the recent years, LabVIEW has been used in scientific and engineering practice for a wide range of applications. For example, industrial purpose like a temperature sensor, level sensor, pressure sensor etc. Virtual Instruments (VIs) are used in LabVIEW instead of programs. LabVIEW enables easy creation of front panel user interface and interactive control of the system. Functionalities are realized by assembling block diagrams. Presently, LabVIEW is a fully featured programming language produced by National Instruments. It is a graphical language by which code is constructed and saved. There is no text-based code, but a diagrammatic view of how the data flows through the program. Thus, LabVIEW is a beloved tool of the scientists and engineers who can often visualize data flow rather than how a text based conventional programming language must be built to achieve a task. Through this dissertation, the efforts have been made to introduce the concept of filtering, compare analog and digital filters, describes finite impulse response (FIR) and infinite impulse response (IIR) filters, and how digital IIR filter can be designed using LabVIEW.
Keywords: LabVIEW; IIR filter